Mapping physical activity research in reputable international journals: a bibliometric analysis - Karisdha Pradityana; Widiastuti Widiastuti; Samsudin Samsudin; Yasep Setiakarnawijaya; Khaeroni Khaeroni (Indonesian Journal of Research in Physical Education, Sport, and Health, 2023)
Background: An in-depth understanding of how physical education can catalyze physical activity among students and society at large is becoming increasingly important. Objective: This study aims to determine the development of scientific publications, mapping the scope and theme of publications related to physical activity published in Scopus-indexed journals from 2018 to 2022. The research questions in this study are: (1) How is the development of publications related to physical activity? (2) What are the most cited articles by title? (3) What themes are related to physical activity? (4) What themes are the most interesting to research in the future? Methods: The publish or perish tool is used to access the Scopus database, which is used in this study. Using the keyword "physical activity," 200 articles were published in Scopus-indexed journals. Keyword co-occurrence analysis is used in this study to find and investigate the primary fields and subjects covered in publications. VosViewer is the program that was used to analyze the data. Results: Publications about physical activity tend to need to be more developed. The work by author Piercy, published in JAMA - Journal of the American Medical Association, has received the most citations out of the 200 published articles. Exercise, mental health, COVID-19, and public health are related topics. Researching several themes about the relationship between physical activity and mental health is intriguing. There has yet to be much research done on physical activity in Indonesia, according to the analysis of publications on the subject that show a tendency to decline in Scopus-indexed journals. This presents an opportunity to investigate physical activity in Indonesia, particularly regarding mental health. Conclusion: It was intended that this development would serve as a guide for soccer coaches in mentoring athletes, particularly those at grassroot age.